Kant and Hegel on freedom - Göksel, Gülay Uğur (Kaygı, 2021)
ABSTRACT: Abstract The main objective of this article is to understand Hegelian understanding of freedom through a comparison of its Kantian counterpart. I set up this investigation with a consideration of the debate between liberals and communitarians. In the history of political thought, many political thinkers have been occupied by the questions about the priority of right over good and of universal over particular. In order to answer these questions, one needs to have a clear conception of freedom since the claims of freedom and equality are universally accepted political values which should reflect our political institutions contextually. To accomplish this task, first, I will introduce a brief account of Kant’s idea of freedom. It is crucial to know Kantian idea of freedom and how this idea reflects to his political philosophy to understand Hegel’s emphasis on ethical order and particularly state institutions. Second, I will give a brief account of Hegel’s idea of freedom by giving references to his book titled Philosophy of Right. Third, I will introduce two major criticisms that Hegel poses to the Kantian idea of freedom. Finally, I will introduce how Hegel tries to overcome the problems of Kantian idea of freedom through the dialectical construction of the concepts of spirit, freedom and ethnical order.

ÖZET: Bu makalenin esas amacı, Kant ve Hegel’in özgürlük anlayışları karşılaştırmalı olarak analiz etmektir. Bu analiz toplum ve birey arasındaki ilişkiyi liberal ve komüniteryan perspektiflerin arasındaki tartışma dikkate alınarak kurgulanmıştır. Siyasal düşünce tarihinde, birçok düşünür, “haklar ile iyi hayatın” ve “evrensel ile pratiğin” arasında seçim yapmak zorunda kalmış ve bu ikilikler arasında hangisinin önceliği olduğu hakkında çözülmesi bir hayli zor sorularla meşgul olmuştur. Bu sorulara cevap verebilmek için, özgürlük anlayışının kesin hatlarla çizilmesi gerekir çünkü özgürlük ve eşitlik siyasi kurumlarımızı yansıması gereken normatif ve evrensel değerlerdir. Bu makalede, ilk olarak, Hegel'in etik düzene ve özellikle devlet kurumlarına yaptığı vurguyu anlamak için Kantçı özgürlük anlayışını ve bunun siyaset felsefesine nasıl yansıdığını bilmek gerektiğinden, Kant’ın özgürlük fikrinin kısa bir açıklamasını sunacağım. İkinci olarak, Hegel’in özgürlük anlayışı Hukuk Felsefesi kitabından atıfla anlatılacaktır. Üçüncü olarak, Hegel'in Kantçı özgürlük fikrine sunduğu iki büyük eleştiri tartışılacaktır. Son olarak, Hegel'in Kantçı özgürlük anlayışının yol açtığı temel eleştirileri; ruh, özgürlük ve etik düzen kavramlarının diyalektik inşası yoluyla nasıl aşmaya çalıştığı gösterilecektir.
Kant ve Hegel’in felsefesinde özgürlük
Keywords: Kant; Hegel; Freedom; Communitarians Philosophy; Philosophy of Right; Özgürlük; Komünitaryan Felsefe; Hukuk Felsefesi